A Content Based Analysis of Cultural Depictions in English Textbook - Akram, Umar Farooq; Arslan, Muhammad Farukh (Basic and Applied Education Research Journal, 2024)
The role that culture plays in teaching English as a global language is complicated by the language's widespread usage in a variety of international situations. Using a well-known paradigm of cultural representation in ELT textbook design by PCTB for grade 9, this study focused on a content analysis of four categories: objects, practices, viewpoints, and persons. The researcher has used qualitative research methods and content analysis as a tool for the analysis. Cultures, which are made up of a society's behavioural patterns that include details about common daily activities and rituals. The variety of foreign cultures that were depicted in these textbooks was obviously unbalanced. This is explained by the fact that the cultures of English-speaking nations are normal in comparison to other civilizations across the globe. It is believed that using English as an international language can help students become more proficient in cross-cultural communication and improve their intercultural competency.If writers of instructional materials focus more on the significance of global culture, this can be made achievable. By using content analysis method the research has evaluated the content of the textbook.